Characterization of CaSiO3:Ce crystals for α- and X-ray detection. (10th November 2021) - Nakamura, Fumiya; Kantuptim, Prom; Nakauchi, Daisuke; Kato, Takumi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: CaSiO3 crystals doped with 0.5%, 1.0% and 2.0% Ce were developed using the floating zone method, and the scintillation and thermally-stimulated luminescence (TSL) properties were evaluated. Under X-ray irradiation, the emission peaks due to the 5d–4f transitions of Ce 3+ appeared at 360 nm in all the samples. Under 241 Am 5.5 MeV α -ray irradiation, a clear full-energy peak appeared in all the samples, and the light yield of the 2.0% Ce doped-sample was 1040 ph/5.5 MeV- α . As a TSL dosimeter, the samples were very sensitive to X-rays and showed a good linear response from 0.1 to 1000 mGy, which was equivalent to the measurable sensitivity of commercial dosimeters for personal dose monitoring.